Prognostic value of the Kyoto Prognostic Index in higher-risk diffuse large B-cell lymphomas treated by upfront autologous stem cell transplantation in JCOG0908 trial. (30th March 2022) - Kobayashi, Tsutomu; Yamamoto, Kazuhito; Kagami, Yoshitoyo; Machida, Ryunosuke; Miyazaki, Kana; Nakamura, Shigeo; Kuroda, Junya; Maruyama, Dai; Nagai, Hirokazu
Abstract: Background: There is currently no standard prognostic model optimized for the patients with diffuse large B-cell lymphoma (DLBCL) treated with upfront intensive immunochemotherapy including autologous stem cell transplantation (ASCT). The Kyoto Prognostic Index (KPI) has been proposed as a novel prognostic model for DLBCL, which can accurately identify especially high-risk patients. In this study, we investigated the prognostic value of the KPI in JCOG0908 trial in which higher-risk DLBCL patients defined by the conventional International Prognostic Index (IPI) were treated with upfront high dose therapy followed by ASCT. Methods: Fifty-eight patients with DLBCL, not otherwise specified, enrolled in JCOG0908 and confirmed by the central pathological review were analyzed. The Kaplan–Meier method was used to estimate the probabilities of overall survival (OS) and progression-free survival (PFS). We compared the discrimination ability of the KPI with that of the IPI. Results: According to KPI, 3-year OS and PFS rates were 86.7% and 76.7% in low-intermediate, 73.3% and 60.0% in high-intermediate, and 61.5% and 46.2% in high-risk group. According to IPI, 3-year OS and PFS rates were 75.0% and 50.0% in low-intermediate, 82.9% and 74.3% in high-intermediate, and 63.6% and 54.5% in high-risk group. The concordance-indices of KPI and IPI were 0.642 and 0.580 for OS and 0.606 and 0.606 for PFS. Conclusions: The KPI may be a suitable predictor of outcome than the IPI for patients with higher-risk DLBCL treated with upfront intensive immunochemotherapy including ASCT. Abstract : The Kyoto Prognostic Index may be a suitable prognostic tool for patients with higher-risk diffuse large B-cell lymphoma treated with upfront high dose therapy with autologous stem cell transplantation.